My Village My Pride A concept towards better India - Mukherjee, Anirban; Maity, Aniruddha (Indian Farming, 2016)
My Village My Pride is a concept visualised for making the agricultureextension programmes more successful. According to the concept,all the extension scientists, professors and students in agricultural field have to select a village to create awareness among farmers about various innovations, technologies and initiations in agriculture.